The unconscious : theory, research, and clinical implications - Weinberger, Joel L. (Guilford Publications, 2019)
"Weaving together state-of-the-art research, theory, and clinical insights, this book provides a new understanding of the unconscious and its centrality in human functioning. The authors review heuristics, implicit memory, implicit learning, attribution theory, implicit motivation, automaticity, affective versus cognitive salience, embodied cognition, and clinical theories of unconscious functioning. They integrate this work with cognitive neuroscience views of the mind to create an empirically supported model of the unconscious. Arguing that widely used psychotherapies--including both psychodynamic and cognitive approaches--have not kept pace with current science, the book identifies promising directions for clinical practice. Subject areas/Key words: unconscious processes, human consciousness, psychoanalysis, psychoanalytic theory, implicit learning, implicit memory, implicit motivation, automaticity, cognition, subconscious, psychodynamic psychotherapy, mind, computational neuroscience, empirical research Audience: Clinical psychologists, psychiatrists, psychoanalysts, and other mental health practitioners, as well as researchers and students of clinical and personality psychology and psychopathology"-- Provided by publisher.
Keywords: Subconsciousness.; Cognitive neuroscience.; Inconscient.; Neurosciences cognitives.; unconscious.; Psychiatry.; MEDICAL.; Social Work.; SOCIAL SCIENCE.; Movements.; PSYCHOLOGY.; Cognitive neuroscience; Subconsciousness